Magnetic Properties of the Spinel Ferrite MgZnFe2O4 Deposited on Glass Using Pulsed-Laser Ablation Method - Lazem, Taha Hussein; Kadhim, Kadhim J.; A., Atheer I. (Al-Mustansiriyah Journal of Science, 2020)
Sol-gel deposition of spinel ferrite MgZnFe2O4 on glass substrate using pulsed- laser ablation method was investigated. The magnetic properties were studied without the addition of any adhesive or fixative. Two samples of thicknesses of (585 nm and 265 nm) ±20 were fabricated. The microwave absorption of the samples was measured at X-band within a frequency range of (8-12.5GHz). The frequency absorption and its relationship with the thickness are addressed.